Development of Graphical User Interface (GUI) for Antenna Design - Cheow , Yeng Peng (IRC, 2016)
This project is to develop a Graphical User Interface (GUI) for the synthesis and analysis of antenna. Antenna design involves electromagnetic wave theory, which takes a tedious process in solving the integral and differential equations. Besides, the introduction of new antenna elements has added to the complexity of antenna, which in turn slower down the antenna design process. Thus, GUI is a crucial tool to speed up the antenna design process, at the same time providing the synthesis and analysis of antenna performance. This project involves four main phases, which is the theoretical modeling of antenna, critical review design of antenna, implementation of synthesis algorithm of antenna and the GUI development. The methodology of this project involved the selection of antenna types to design, computation of antenna parameters, analysis of antenna performance and lastly end with the impedance matching solution. In this project, impedance matching is essential in determining the suitability of an antenna as a matched antenna network, ensuring a maximum power transfer of signal source to the load.